PENERAPAN NILAI-NILAI PANCASILA DALAM KEBUDAYAAN MASYARAKAT INDONESIA (STUDI KASUS TRADISI DUNDUNAN DI JAWA TENGAH) - Sihombing, Daniel Romi; Naaila, Callysta Nur; Sihombing, Denissa Angela (Jurnal TEDC; Vol 19 No 2 (2025): JURNAL TEDC, 2025)
Pancasila has values ​​related to people's social and cultural lives. The aim of this research is to study how Pancasila values ​​are applied in the Dundunan tradition in Central Java, which is part of the local culture. The Dundunan tradition greatly influences the spiritual and social life of the community, which includes various ceremonies and customs. This study identifies how the practices and philosophies in the tradition translate the values ​​of Pancasila, especially in terms of divinity, humanity, unity, democracy and social justice. This research found that Pancasila values ​​are reflected implicitly in every aspect of the Dundunan tradition, which increases a sense of togetherness, solidarity and respect for nature and other people. This research was conducted using a qualitative approach and participatory observation methods. This study shows that Pancasila is not only a state ideology, but more than that.